Translation in language learning: a ‘what for’ approach - Balboni, Paolo E. (2017)
Literature about translation in language learning and teaching shows the prominence of the ‘for and against’ approach, while a ‘what for’ approach would be more profitable. In order to prevent the latter approach from becoming a random list of the potential benefits of the use of translation in language teaching, this essay suggests the use of a formal model of communicative competence, to see which of its components can profit of translation activities. The result is a map of the effects of translation in the wide range of competences and abilities which constitute language learning.